Effect of Chemotherapy on Gonadal Function and Sexual Function of Male Cancer Survivors: A Review Article - Sodeifian, Fatemeh; Kian, Naghme; Baghsheikhi, Hediyeh; Allameh, Farzad (Urology Journal, 2024)
Purpose: The advancement of anti-cancer treatment has increased survival rates among patients, yet putting them in an increased risk for developing side effects. In addition to early side effects, anti-cancer treatments, in particular chemotherapeutic medications can cause long-term side effects; fertility and sexual dysfunction included. The aim of this study was to review existing data on the effects of different chemotherapeutic agents on fertility and sexual function of male cancer survivors who received chemotherapy at different stages of life. Methods: We searched PubMed/MEDLINE, Scopus, and Google Scholar to detect studies focused on the effect of chemotherapy on the gonadal/testicular function and sexual function of male cancer survivors. We restricted our search to English language publications and manuscript published before the year 2000 were excluded. Results: It has been well understood that chemotherapy impairs gonadal function in a major number of cancer survivors and gonadal dysfunction is not protected if chemotherapeutic agents are administered before puberty in males. Moreover, the effect of chemotherapy on sexual function is controversial. Conclusion: While several articles reported the worst effect of chemotherapy on the sexual function of cancer survivors, some studies reported that chemotherapy does not impair sexual function. Higher levels of chemotherapy dose seem to be associated with more gonadal and sexual dysfunction.